Actual Self-Image Versus Ideal Self-Image: An Exploratory Study of Self-Congruity Effects on Gambling Tourism - Li, Mao-Hua; Lai, Ivan Ka Wai (Frontiers in Psychology, 2021)
This study aims to apply self-congruity theory to examine the relationship between tourists’ self-congruity and their perceived image of a gambling destination. This study employs the Euclidean distance model and extends Malhotra’s pars of adjectives with five new items about gambling motives. A face-to-face questionnaire survey was used and a total of 152 samples were collected from tourists in Macau. The results show that tourists’ actual self-image is more related to their perception of Macau image. For actual congruence, tourists exhibit a greater tendency to match the informal, liberal, and emotional image of Macau. For ideal congruence, they have a tendency to match the contemporary, organized, and pleasant image of Macau. This study makes up for the deficiency of self-congruity theory in tourism research. This study helps tourism departments to develop appropriate strategies to promote gambling tourism and disseminate relevant information that can bring gambling destinations closer to tourists.